Karakteristik Interjeksi Dalam Serial Animasi Nussa Dan Rarra: Kajian Morfologis - Fadillah Andini; Agustina (Universitas Negeri Padang, 2023)
The aim of this research is to, (1) describe the form of interjection in animated series Nussa and Rarra. (2) describe the types of interjections in animated series Nussa and Rarra. This research is qualitative research and uses descriptive methods by describing the data found to obtain general conclusions. The data used in this research are sentences containing morphemes, words and interjection phrases which were downloaded through animated series Nussa and Rarra. The first result found is the form of interjection in Nussa and Rarra animated series consists of two forms, the basic form (20 data) and the derivative form (7 data). Second, based on types, eight types were found, (1) exclamation interjections namely ayo, eh, ehm, yuk, halo, (2) astonishment or admiration interjections namely masyaallah, hm, wah, hah, oh, uh, haduh, iya ya, alhamdulillah, lho, (3) sadness interjections namely aduh, uh, hm, (4) sadness interjections namely ih, hm, hadeh, eh, aduh, wah, astagfirullah, (5) disappointment and annoyance interjections namely ih, hm, hadeh, eh, aduh, wah, astagfirullah, (6) surprise interjections namely hah, aduh, wah, eh, astagfirullah, ih, ya ampun, astaghfirullah 'al-‘adziim, waduh masyaallah, ah, (7) relief interjections namely alhamdulillah, nah, haah, aha, hm, insyaallah, and (8) disgust interjection namely ihh.